Tawhid-Based Curriculum Management in Social Care Character Building (Study At SDIT Labschool Al Fatah Bekasi City) - Darmadi, Didi; Suharyat, Yayat; Muthi, Ibnu (Proceeding International Conference on Education, 2023)
This study aims to determine the management of the Tawhid Curriculum implemented at SDIT Labschool Al Fatah Bekasi city, which includes, planning, organizing, implementing and evaluating. This research uses a qualitative approach with a descriptive method. Data collection techniques with observation, interviews and documentation studies. Data analysis using Miles and Hubberman analysis. The results of the study describe the management of the Tawhid curriculum including: 1). Planning, organizing, implementing, and evaluating the curriculum has been going well, but it still needs to be improved to make it even better. 2). The inhibiting factors faced, among others; Limited resources, diverse acceptance and understanding from stakeholders, with solutions including conducting training and optimizing the use of existing resources and conducting effective communication 3). The social care character of students is good, this is evidenced by the many social activities carried out. From this research, it can be concluded that the management of the tawhid curriculum implemented needs to be improved.